Possibilities and limitation of prenatal diagnosis and carrier determination for Duchenne and Becker muscular dystrophy using cDNA probes. - Speer, A (1989)
Two cDNA probes, cf23a and cf56a, identify deletions of selected exons in about 50% of our DMD/BMD patients. We have estimated the most likely order of the 11 exons detectable with both probes with respect to the different extensions of the deletions. In one of our BMD pedigrees, the observed deletion could be traced in the affected males through three generations. This result shows that with the use of cDNA probes detecting deletions, the only risk of error in genomic prenatal diagnosis is the general high frequency of new mutations for DMD/BMD. This is important progress in diagnosis compared to the 2 to 5% risk of misdiagnosis because of crossing over events using conventional linkage analysis with bridging or intragenic probes. The first prenatal diagnosis of an unaffected fetus of a woman who is a DMD carrier according to ultrasound examination is described. In one of our DMD males, the cDNA probe cf56a detects a deletion breakpoint. His sister also shows the altered band and is therefore a DMD carrier, while his mother has a totally normal band pattern. The interpretation of this observation could be either germline mosaicism or two identical new mutations. The identification of deletion breakpoints is a new diagnostic strategy, especially for carrier determination, which excludes misdiagnosis owing to crossing over events and the problems of dosage estimation. It is, however, limited by the low frequency of breakpoints detectable with cDNA probes. Therefore, the generation of new intron probes in this region is an important goal.